Topics of the press column in Al-Sabah newspaper For the period from 1/12 to 31/12/2008 Analytical study (Journal of the College of Basic Education, 2022)
The press column is considered one of the important journalistic arts that most newspapers used to use.on its pages, as it receives special care from the editorial boards in highlighting the writers' opinions and positions. on a particular issue or event.What increases the importance of this journalistic art is the reader's feeling that he is close to him and his problems.his concerns and offers effective solutions to them and enhances the connection, relationship and response between the reader on the one hand health and books on the other hand.